Implementing Green Constitution: Assessing the Policy of Plastic Waste Payment in Suroboyo Bus Service - AlMusyaawi, Muchammad Ibnu Shiina; Sarbini, Sarbini; Ningsih, Erlin Indaya (International Journal of Law Dynamics Review, 2024)
This article explores the plastic waste-based payment policy implemented on the Suroboyo Bus Service in Indonesia, examining its alignment with the principles of a Green Constitution. The Green Constitution concept emphasizes the integration of environmental protection into legal frameworks. This study aims to analyze the Suroboyo Bus Service Plastic Waste Payment Policy in the context of the Green Constitution. Our analysis covers various aspects, including the historical background, legal norms, policy effectiveness, and the importance of community participation. The study employs normative-empirical research methods, examining the legal norms underpinning the Suroboyo Bus Service policy and its implementation. Quantitative data is collected through questionnaires distributed to the Suroboyo Bus Service users, revealing insights into public awareness, attitudes, and perceptions regarding the policy. Analysis of legal norms indicates a harmonization between the Suroboyo Bus Service policy and the Green Constitution principles outlined in the 1945 Indonesian Constitution. However, the study identifies a legal vacuum in waste management, suggesting more explicit guidelines are needed. The article also underscores the importance of collaborative efforts between the government and community organizations in efficient waste management.